A Survey of Environmental Radioactivity Levels in Science Laboratories of Abuja Campus University of Port- Harcourt, Nigeria - C. P. Ononugbo; M. Ishiekwene (Archives of Current Research International, 2017)
An in-situ measurement of the background radiation level was carried out at the science laboratories, Ofrima, Abuja campus of University of Port Harcourt, Nigeria. This study was carried out to evaluate the radiological health impact of radiation exposure of staff and students that uses such laboratories. Two portable radiation meters (digilert-200 and Radalert-100) survey meters was used to measure the background radiation levels of the laboratories (indoor and outdoor). The indoor and outdoor exposure rates measured was converted to absorbed dose in nano Grays per hour. The average annual effective dose equivalent of the three major laboratories (Physics, pharmacy and environmental microbiology) estimated are 0.165 ±0.002, 1.109± 0.010 and 0.56 ± 0.02 mSvy-1 respectively and their corresponding absorbed dose rates are 119.92, 111.69 and 115.10 nGyh-1 respectively. The excess lifetime cancer risks of the three laboratories are 0.512 × 10-3, 1.25 × 10-3 and 2.03 ×10-3. From the results, the indoor average annual effective dose equivalents were lower than their permissible safe limit of 1.0 mSvy-1 except for pharmaceutical laboratory which recorded slightly mean higher value of 1.109 mSvy-1. The indoor absorbed doses and excess lifetime cancer risk determined were higher than their permissible values. The outdoor exposure rate of 14.14 µRh-1 was recorded and absorbed dose rate of 117.24 nGyh-1 was estimated. The average outdoor annual effective dose obtained is 0.150 mSvy-1 and excess lifetime cancer risk of 0.525 × 10-3 was obtained. Indoor radiation levels and their associated risk parameters are higher than the outdoor counterpart which is an indication of the radiation emission from chemicals and equipment in the laboratories. The results of this study shows that there is no immediate radiological health risk to workers and students. The study will serve as radiation baseline data for those studied laboratories for future studies.